STUDI ISLAM MELAYU: Melacak Karya-karya Kyai H. Anwar Seribandung-Palembang - Hafidhuddin Hafidhuddin (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
South Sumatra, socially intellectual, is one area that has a tradition of writing that is strong enough. Many found religious books or other themes that are found in this area. The abundance of these writings can not be released to the role of the scholars who actively and creatively to formulate the teachings of Islam to the people. This tradition is experiencing dynamic development along with the development of his time. The tradition of writing in South Sumatra typical